Comprehensive management of anterior drooling: An International Pediatric Otolaryngology Group (IPOG) consensus statement. (May 2023) - Daniel, Sam J.; Fayoux, Pierre; Bateman, Neil; Boudewyns, An; Brigger, Matthew; Chan, Ching Yee; Chan, Kenny; Cheng, Alan; Conley, Stephen; Kubba, Haytham; Lambert, Elton M.; Muntz, Harlan; et al.
Abstract: Objective: To provide guidance for the comprehensive management of children referred for anterior drooling. The mission of the International Pediatric Otolaryngology Group (IPOG) is to develop expertise-based recommendations for the management of pediatric otolaryngologic disorders with the goal of improving patient care. Methods: Survey of expert opinion by the members of the International Pediatric Otolaryngology Group (IPOG). The recommendations are derived from current expert consensus and critical review of the literature. Results: Consensus recommendations include initial care and approach recommendations for health care providers who commonly evaluate children with drooling. This includes evaluation and treatment considerations for commonly debated issues in drooling management, initial work-up of children referred for anterior drooling, treatment recommendations, indications and contra-indications for rehabilitation, medical, and surgical management, as well as pros and cons of different surgical procedures in the hands of drooling management experts. Conclusion: Anterior drooling consensus recommendations are aimed at improving patient-centered care in children referred for sialorrhea.